2006
DOI: 10.3136/fstr.12.137
|View full text |Cite
|
Sign up to set email alerts
|

Psicose Contents in Various Food Products and its Origin

Abstract: To elucidate the history of human exposure of psicose, a determination method of psicose (D/L-psicose) in various food products has been developed : post column high-performance liquid chromatography (HPLC) using gel permeation column in ligand exchange mode coupled with pulsed amperometric detection (PAD). The calibration curve of D-psicose was linear in a concentration range of / to +/* mg/ml with a correlation coe$cient of *.3333. With ultrasonic extraction and C+2 Sep-pack filtration methods, the samples f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
84
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(88 citation statements)
references
References 13 publications
1
84
0
Order By: Relevance
“…Previously (Oshima et al, 2006) we reported that psicose is found in various food products and suggested that the sugar was produced from fructose or sucrose under ordinary heating conditions. Moreover, based on the psicose concentration in food products, we expected that the sugar concentration, heating time, and temperature during the manufacturing process influence the concentration of psicose in food products.…”
Section: Introductionmentioning
confidence: 99%
“…Previously (Oshima et al, 2006) we reported that psicose is found in various food products and suggested that the sugar was produced from fructose or sucrose under ordinary heating conditions. Moreover, based on the psicose concentration in food products, we expected that the sugar concentration, heating time, and temperature during the manufacturing process influence the concentration of psicose in food products.…”
Section: Introductionmentioning
confidence: 99%
“…35) By baking, a D psicose containing butter cookie has recently been shown to gain antioxidant activity due to the browning reaction. 36) D Psicose can lower plasma glucose levels and reduce body fat accumulation in rats, suggesting suppression of the hepatic lipogenic activity 37) and may also be of therapeutic value in the treatment of diseases such as atherosclerosis.…”
Section: D-psicosementioning
confidence: 99%
“…The control and PS diets included 3% D-psicose in CE-2, a commercial rodent chow (CLEA). The amount of test carbohydrates was determined with reference to previous studies concerning D-psicose [13] or sucralose, the LD 50 of which is the same as that of D-psicose [17,18]. Each group of rats was given free access to food and water for 90 days.…”
Section: Animals and Experimental Dietsmentioning
confidence: 99%
“…Oshima et al [13] reported that in highsugar food products, heat processing had a marked effect on the production of D-psicose. In particular, con-fectionery products and seasoning sauces exhibited higher D-psicose content (0.005 -1.3 mg/g) than other products [13]. As a result, most people ingest a limited amount of D-psicose on a daily basis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation